Kebijakan Pemerintah Terhadap Belt And Road Initiative (BRI) Dalam Paradigma Ekonomi Syariah - Hendra Yulia Rahman (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractionBilateral relations between Indonesia and China have been established since the past, and have experienced ups and downs. After the reform period, bilateral relations were re-woven, beginning with the recognition of the religion of Konghucu as the official religion in Indonesia by President Abdurrahman Wahid, and imlek becoming a holiday and national holiday. Bilateral relations intensified in the government of President Jokowidodo, with the cooperation policy of Belt and Road Initiative (BRI). The policy raises hopes and concerns at the same time. The author will discuss related to the theme including: first, what is meant by the Belt and Road Initiative (BRI). Second, discussing Islamic economics, thirdly, how government policy is against the Belt and Road Initiative (BRI), and fourth, government policy on the Belt and Road Initiative (BRI) in the Islamic economic paradigm. The analysis uses the concept of maslahah in maqashid sharia.Keywords: policies, Belt and Road Initiative, welfare (falah) maslahah, shariaAbstraksiHubungan bilateral Indonesia dan China sudah terjalin sejak masa lampau, serta mengalami pasang surut. Setelah masa reformasi, hubungan bilateral kembali dirajut, diawali dengan pengakuan agama konghucu sebagai agama resmi di Indonesia oleh Presiden Abdurrahman Wahid, dan imlek menjadi hari raya dan libur nasional. Hubungan bilateral semakin meningkat dipemerintahan Presiden Jokowidodo, dengan kebijakan kerjasama Belt and Road Initiative (BRI). Kebijakan tersebut menimbulkan harapan dan sekaligus kekhawatiran. Artikel ini akan membahas berkaitan dengan tema tersebut diantaranya: pertama apakah yang di maksud dengan Belt and Road Initiative (BRI). Kedua, membahas ekonomi syariah, ketiga, bagaimana Kebijakan pemerintah Terhadap Belt and Road Initiative (BRI), dan keempat, Kebijakan pemerintah Terhadap Belt and Road Initiative (BRI) dalam Paradigma ekonomi syariah. Analisis menggunakan konsep maslahah dalam maqashid syariah.Kata kunci: kebijakan, Belt and Road Initiative, kesejahteraan (falah) maslahah, syariah